When Proficiency and Education Matter: The Mediating Role of English Proficiency and Moderating Effect of Parents' Education in the SES–Academic Achievement Relationship During EMI. (June 2022) - Muttaqin, Syariful; Chuang, Hsueh-Hua; Lin, Ching-Hui; Cheng, Ming-Min
This study investigated how socioeconomic status (SES) is associated with academic achievement and English proficiency in an English-medium instruction (EMI) program at a state university in Indonesia. It also examined the mediating effect of English proficiency and moderating effect of parents' education on the relationship between SES and academic achievement. Data for 234 EMI students were obtained from the academic office of the university. Based on mediation analysis, SES significantly predicted students' academic achievement and English proficiency. However, it stopped being a significant predictor when mediated through English proficiency. The moderation analysis shows that the degree of increase in EMI students' grade point average was affected by the level of parents' education when associated with family income. The article also presents the implications of the findings in enhancing university EMI programs and suggestions for future research.